Ecoenzym: Inovasi Pengelolaan Sampah Organik di Ma’had Tafaqquh - Sri Wahyuni; Martalasari, Martalasari; Asrori, Ikrima; Putra, Rengga Meinanda; Djamaludin, Aldian (Universitas Lancang Kuning, 2025)
Eco-enzyme is an environmentally friendly product made from fruit peels, vegetables, and sugar, which are fermented with water for three months. It can be used for cleaning, deodorizing, pest control, soil improvement, and water conservation. Eco-enzyme has various benefits, particularly in the production of disinfectants. It can also serve as an alternative to chemical substances that are harmful to the environment and human health. The raw materials for eco-enzyme come from organic waste that is no longer utilized and is often considered useless. Organic materials such as fruit peels or vegetable scraps can be used as raw materials in the production of eco-enzyme. The practice of producing and utilizing eco-enzyme in Islamic boarding schools, particularly at Ma’had Tafaqquh, is still not widely known or thoroughly studied. Therefore, this community service project aims to empower students by organizing training or workshops on the process of making eco-enzyme as a natural disinfectant. This community service activity is expected to contribute to the greenery and cleanliness of the pesantren environment while educating students about environmental awareness programs in society, particularly within Islamic boarding schools. Following the implementation of the community service activity, it was observed that the students were highly enthusiastic about participating in the training and workshop. Ma’had Tafaqquh is committed to maintaining a green and clean pesantren environment through proper waste management.